The Influence of Store Atmosphere, Promotions and Location on Buying Interest in Indah Sari Pematang Siantar Store in 2024 - Tarigan, Adrian K; Nainggolan, Anju Bherna D (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
StudyThis aims to determine the influence of shop atmosphere, promotions and location on purchasing interest at the Indah Sari Pematang Siantar shop. This research is survey research using a questionnaire as the instrument. The population used in this research was consumers of Toko Indah Sari Pematang Siantar in Banjarnegara city. The sample used was 130 consumers of Toko Indah Sari Pematang Siantar in Banjarnegara city using the Purposive Sampling method. Test the validity of the instrument using Confirmatory Factor Analysis and test its reliability using Cronbach's Alpha. . The analysis technique used is multiple regression analysis. The research results found that: (1) Store atmosphere has a positive effect on buying interest. (2) Promotion has a positive effect on buying interest. (3) Location has a positive effect on buying interest. (4) Store atmosphere, promotions and location have a positive effect on buying interest. The magnitude of the influence of store atmosphere, promotions and location on purchase interest (adjusted R2) is 0.467.